Coupled large-strain mechanochemical theory for solid-state reaction with application to oxidation. (November 2021) - Attariani, Hamed; Levitas, Valery I.
Graphical abstract: Abstract: Oxidation is still perceived as a significant challenge in various industrial applications, e.g., pressurized water reactors and gas-turbines. One of the hurdles in understanding oxidation is its coupled multi-physics nature, i.e., the coupling between mechanics, chemical reaction, change in the microstructure, and diffusion. Here, a general large-strain mechanochemical theory is developed to model the anisotropic reaction/compositional strain in the solid-state chemical reaction. This novel stress-relaxation is achieved by introducing a kinetic relationship between deviatoric reaction deformation rate and the deviatoric Cauchy stress. Also, a new chemical potential and the expression for the driving force for the chemical reaction, including the deviatoric stress, are derived. The new model shows that the deviatoric stress alters the chemical equilibrium constant and reaction rate through reaction-induced deviatoric stress. Finally, the developed mathematical framework is used to study the aluminum oxidation for model calibration and verification; results are in good agreement with existing experimental studies.